Is Africa's Economy at a Turning Point? - Arbache, Jorge; Go, Delfin S.; Page, John (World Bank, Washington, DC, 2012)
In this paper, Arbache, Go, and Page examine the recent acceleration of growth in Africa. Unlike the past, the performance is now registered broadly across several types of countries-particularly the oil-exporting and resource-intensive countries and, in more recent years, the large- and middle-income economies, as well as coastal and low-income countries. The analysis confirms a trend break in the mid-1990s, identifying a growth acceleration that is due not only to favorable terms of trade and greater aid, but also to better policy. Indeed, the growth diagnostics show that more and more African countries have been able to avoid mistakes with better macropolicy, better governance, and fewer conflicts; as a result, the likelihood of growth decelerations has declined significantly. Nonetheless, the sustainability of that growth is fragile, because economic fundamentals, such as savings, investment, productivity, and export diversification, remain stagnant. The good news in the story is that African economies appear to have learned how to avoid the mistakes that led to the frequent growth collapses between 1975 and 1995. The bad news is that much less is known about the recipes for long-term success in development, such as developing the right institutions and the policies to raise savings and diversify exports, than about how to avoid economic bad times.